Answer:
[tex]X=X_o+\dfrac{1}{2}gt^2[/tex]
Explanation:
Given that
Length = L
At initial over hanging length = Xo
Lets take the length =X after time t
The velocity of length will become V
Now by energy conservation
[tex]\dfrac{1}{2}mV^2=mg(X-X_o)[/tex]
So
[tex]V=\sqrt{2g(X-X_o)}[/tex]
We know that
[tex]\dfrac{dX}{dt}=V[/tex]
[tex]\dfrac{dX}{dt}=\sqrt{2g(X-X_o)}[/tex]
[tex]\sqrt{2g}\ dt=(X-X_o)^{-\frac{1}{2}}dX[/tex]
At t= 0 ,X=Xo
So we can say that
[tex]X=X_o+\dfrac{1}{2}gt^2[/tex]
So the length of cable after time t
[tex]X=X_o+\dfrac{1}{2}gt^2[/tex]